It is not all bad for the grey city – A crossover study on physiological and psychological restoration in a forest and an urban environment. (July 2017) - Stigsdotter, Ulrika K.; Corazon, Sus Sola; Sidenius, Ulrik; Kristiansen, Jesper; Grahn, Patrik
Abstract: Today, urbanization presents a challenge to urban planning with regard to creating healthy living environments. The aim of this research is to gain further knowledge of the restorativeness of a best case urban and natural environment: that is a historic down town urban environment and forest environment located in an arboretum. The study has a cross-over design where 51 (N) female university students are exposed to the two environments through both seated viewing and walking. A mixed method approach is used with both physiological measurements of blood pressure (BP) and heart rate variability (HRV) and psychological measurements of mood change and perceived restorativeness. The HRV results show no significant differences between the two environments, and both environments are found to be more physiologically restorative than being at the office or on the minibus. The results of the psychological measures indicate that the forest walk has a positive effect on mood, while the walk in the urban environment has no effect. The forest environment is also rated more highly with regard to perceived restorativeness than the urban environment. The results support the current research that shows natural environments as more restorative than urban environments. The study also adds to the ongoing debate on healthy urban planning by indicating that architectural and historical qualities may be associated with the physiological well-being of citizens. Highlights: No difference was found in HRV between the forest and urban environment. The forest environment was perceived as more restorative than the urban environment. Significant correlations were found between perceived restorativeness and mood.